Asking different questions: A call to action for research to improve the quality of care for every woman, every child. Issue 3 (21st June 2018) - Kennedy, Holly P.; Cheyney, Melissa; Dahlen, Hannah G.; Downe, Soo; Foureur, Maralyn J.; Homer, Caroline S. E.; Jefford, Elaine; McFadden, Alison; Michel‐Schuldt, Michaela; Sandall, Jane; Soltani, Hora; Speciale, Anna M.; et al.
Abstract: Despite decades of considerable economic investment in improving the health of families and newborns world‐wide, aspirations for maternal and newborn health have yet to be attained in many regions. The global turn toward recognizing the importance of positive experiences of pregnancy, intrapartum and postnatal care, and care in the first weeks of life, while continuing to work to minimize adverse outcomes, signals a critical change in the maternal and newborn health care conversation and research prioritization. This paper presents "different research questions" drawing on evidence presented in the 2014 Lancet Series on Midwifery and a research prioritization study conducted with the World Health Organization. The results indicated that future research investment in maternal and newborn health should be on "right care, " which is quality care that is tailored to individuals, weighs benefits and harms, is person‐centered, works across the whole continuum of care, advances equity, and is informed by evidence, including cost‐effectiveness. Three inter‐related research themes were identified: examination and implementation of models of care that enhance both well‐being and safety; investigating and optimizing physiological, psychological, and social processes in pregnancy, childbirth, and the postnatal period; and development and validation of outcome measures that capture short and longer term well‐being. New, transformative research approaches should account for the underlying social and political‐economic mechanisms that enhance or constrain the well‐being of women, newborns, families, and societies. Investment in research capacity and capability building across all settings is critical, but especially in those countries that bear the greatest burden of poor outcomes. We believe this call to action for investment in the three research priorities identified in this paper has the potential to achieve these benefits and to realize the ambitions of Sustainable Development Goal Three of good health and well‐being for all.